Hydrothermally synthesized urchinlike NiO nanostructures for supercapacitor and nonenzymatic glucose biosensing application. (1st November 2021) - Pore, O.C.; Fulari, A.V.; Velhal, N.B.; Parale, V.G.; Park, H.H.; Shejwal, R.V.; Fulari, V.J.; Lohar, G.M.
Abstract: Nickel oxide nanostructures with different reaction temperatures were synthesized by the hydrothermal method. The formation of NiO nanostructures confirmed by XRD and FTIR analysis. The urchinlike morphology was confirmed from the FE-SEM analysis. The electrochemical supercapacitive properties are studied by EIS, CV and GCD studies. The electrochemical supercapacitor study confirms that the electrode prepared on flexible copper foil by using urchinlike NiO nanostructure with reaction temperature 150 °C shows maximum specific capacitance of 341.10 F g −1 at 10 mV s −1 scan rate. Also, it offers better capacity retention about 96.3% after 1000 cycles. The NiO nanostructures with reaction temperature 110 °C show glucose sensitivity of 878.6 μA mM −1 cm −2 with LOD 0.37 μM.